Horst Mahler. Biographische Studie zu Antisemitismus, Antiamerikanismus und Versuchen deutscher Schuldabwehr - Fischer, Michael (EUKLID : Europäische Kultur und Ideengeschichte. Studien, 2015)
Horst Mahler was one of the most important participants of the German student movement during the late 1960s. In the 1990s he bacame a radical National socialist and holocaust denier. This conversion still bothers the German public. There are however ideological continuities in Mahler’s worldview: structural anti-semitism, anti-americanism and repetitive attempts to refuse guilt feelings about the holocaust.